Some Coupled Fixed Point Theorems in Modular Metric Space Using Caristi Type Contraction - Adilakshmi, G; N.V.Kishore, G (International Journal of Engineering and Technology, 2018)
In this paper, we obtained a unique common coupled fixed point theorem using Caristi type contraction in modular metric spaces. Also furnished an example to support our main results.Â Â